Genome analysis of a Limnobacter sp. identified in an anaerobic methane-consuming cell consortium - Chen, Ying; Feng, Xiaoyuan; He, Ying; Wang, Fengping (Frontiers in Marine Science, 2016)
Species of Limnobacter genus are widespread in a variety of environments, yet knowledges upon their metabolic potentials and mechanisms of environmental adaptation are limited. In this study, a cell aggregate containing Limnobacter and anaerobic methanotrophic archaea (ANME) was captured from an enriched anaerobic methane oxidizing (AOM) microbial community. A genomic bin of Limnobacter was obtained and analyzed, which provides the first metabolic insights into Limnobacter from an AOM environment. This Limnobacter was found to contain genes involved in the Embden-Meyerhof pathway, the citrate cycle, citronellol degradation, and transporters of various organic substances, indicating a potentially heterotrophic lifestyle. A number of genes involved in sulfur oxidization, oxidative phosphorylation and ethanol fermentation that serve both aerobic and anaerobic purposes have been found in Limnobacter. This work suggests that in the AOM environment, Limnobacter strains may live on the organic substances produced through AOM activity and subsequently may contribute to the AOM community by providing sulfate from sulfur oxidation.